Is Implied Taylor Rule Interest Rate Applicable as a Carry Trade Strategy? - Ogruk, Gokcen (International Journal of Economics and Financial Issues, 2014)
This paper evaluates the performance of carry trade strategies with implied Taylor rule interest rate differentials and compares the performance statistics of them over the naive carry trade strategy with actual interest rates. Carry trade, a currency speculation strategy, between high-interest rate and low-interest rate currencies generates high payoff on average and has a possibility of crash risk. I argue that the crash risk is reduced with implied Taylor rule interest rate differentials as a trading strategy in Yen and Franc trades for the whole sample period. During the recent financial crisis, the carry trading strategies with Taylor rule perform best in terms of mean returns, risk adjusted returns and downside risk. Keywords: Carry Trade; Taylor Rule Fundamentals. JEL Classifications: E32; E37; E43; F31; F37; G15.